Conceptual approaches to the essence and typology of business models in tourism - Tashenova, L.V.; Mamrayeva, D.G. (BUKETOV BUSINESS REVIEW, 2021)
Object: defining the essence and main types of business models in tourism, identifying their structural elements. Methods: for achieving the goal of the research general scientific methods were applied, in particular the method of content analysis, which made it possible to identify the main scientific research related to the study of business models in the field of tourism and hospitality; the method of a systematic approach, which made it possible to identify the main types of business models in tourism, to reveal the integrity of the models; the structural-functional method, with the help of which the structure of the studied business models was highlighted, the set of stable relations and relationships between their elements and their functions relative to each other is reflected; a generalization method aimed at establishing the existing relationships between the considered economic objects and phenomena; the method of graphic interpretation made it possible to visually present the developed business models used by tourist companies. Results: the article reveals the conceptual approaches to the essence of business models in tourism, carried out a content analysis of the definitions of a business model, based on which the author's definition of this category is given. The basic components and system characteristics of the business model are identified. The main types of business models used by travel companies have been developed and clearly presented, in particular a customization model, a «virtual system» model, a «franchise» model, and an innovative business model. The criteria and factors of classification types are systematized, including digitalization, innovation, customer and resource orientation. Conclusions: the results of the research made it possible to deepen the theory of entrepreneurial activity in tourism, expand the conceptual apparatus of the essence and typology of business models in tourism.